Hubungan Perilaku Merokok dengan Kejadian Hipertensi pada Usia Produktif di Wilayah Kerja Puskesmas Jekan Raya Tahun 2022: The Corelation of Smoking Behavior With Hypertension Incidence at Productive Age in the Work Area of Jekan Raya Public Health Center - Niki Efriandi; Rizki Muji Lestari; Dita Wasthu Prasida (Jurnal Surya Medika (JSM), 2023)
Smoking is one of the factors that can cause various health problems, one of which is hypertension. However, in reality there are still many people who still smoke and do not care about the dangers of smoking for their health and those around them so that it becomes a trigger for various diseases, one of which is hypertension. Research Objectives of this study was to analyze the relationship between smoking behavior and hypertension in the working area of ​​the Jekan Raya Public Health Center. The design of this study used a cross sectional method. The sampling method used is purposive sampling. Samples were taken as many as 33 respondents, namely people of productive age who are in the work area of ​​the Jekan Raya Health Center. The research data was taken using an observation sheet and a digital sphygmomanometer, after tabulating the existing data were analyzed using a chi square test analysis assisted by a computer. The results showed that there was no significant correlation between smoking behavior and the incidence of hypertension in the work area of ​​the Jekan Raya Health Center. The analysis of the chi square statistical test obtained p value = 0.643. Although the results of the study have no correlation but still maintain a clean and healthy lifestyle without cigarette smoke, because the substances contained in cigarettes will affect the health of the body and can be a factor causing hypertension.